Construct and content validity of the Turkish Birth Satisfaction Scale – Revised (T-BSS-R). (27th May 2018) - Göncü Serhatlıoğlu, Seda; Karahan, Nazan; Hollins Martin, Caroline J.; Martin, Colin R.
Abstract: Background: The Birth Satisfaction Scale – Revised (BSS-R) is a valid and reliable scale designed to assess women's experiences of labour and childbirth. Objective: To assess factor structure, validity, and reliability of the Turkish Birth Satisfaction Scale – Revised (T-BSS-R) using data collected from a Turkish population. Setting: Istanbul Ministry of Health Zeynep Kamil Women's and Children's Training and Research Hospital. Participants: A convenience sample of healthy child-bearing women ( n = 120) who had experienced a spontaneous vertex delivery at full term. Method: A survey was conducted post backtranslating the T-BSS-R, with survey data analysed using confirmatory factor analysis. Results: Factor modelling found three subscales embedded in the T-BSS-R, which indicated a good model fit, χ 2 = 44.67, CFI = .94; RMSEA = .057; SRMR = .075. A Chi-square value of 1.33 also indicated a good fit. Means for the T-BSS-R subdimensions (1) Stress Experienced (T-BSS-SE-R) = 6.86 ± 3.10, (2) Women's Attributes (T-BSS-WA-R) = 2.84 ± 1.89, (3) Quality of Care (T-BSS-QC-R) = 10.69 ± 3.19 and total scale = 20.39 ± 5.98. The Cronbach alpha coefficient for total scale = 0.71 and for subdimensions T-BSS-SE-R = 0.55, T-BSS-WA-R = 0.44 and T-BSS-QC-R = –0.74. Conclusion: Data analysis determined that the T-BSS-R is a valid and reliable instrument to measure birth satisfaction in a population of Turkish women. The T-BSS-R is available for use fromc.hollinsmartin@napier.ac.uk .